Managerial Autonomy, Allocation of Control Rights, and Optimal Capital Structure - Boot, Arnoud W. A.; Thakor, Anjan V. (Review of Financial Studies, 2011)
We examine the design of control rights of external financiers, and how these interact with the firm's security issuance and capital structure when the firm's initial owners and managers may disagree with new investors over project choice. The first main result is an ex ante managerial preference for “soft” financial claims that maximize managerial project-choice autonomy, which is in contrast to agency theory. Second, a dynamic “pecking order” of cash, equity, and debt emerges. Additional results explain equity issuance at high prices, the drifting of leverage ratios with stock returns, cash hoarding, and debt usage without taxes, agency, or signaling.